2008
DOI: 10.1056/nejmoa0706824
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin and Outcome in Acute Heart Failure

Abstract: In patients with acute decompensated heart failure, a positive cardiac troponin test is associated with higher in-hospital mortality, independently of other predictive variables. (ClinicalTrials.gov number, NCT00366639 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
384
4
18

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 654 publications
(437 citation statements)
references
References 18 publications
31
384
4
18
Order By: Relevance
“…24 The diagnostic performance of GFAP-BDP, as indicated in the current study by receiver operator curve analysis, is on a par with that of troponin in myocardial ischemia and brain natriuretic peptide in congestive heart failure. [25][26][27] Our findings are also consistent with previous reports in terms of predictive power and measured levels of serum GFAP in TBI. 4 We found that serum GFAP-BDP Odds ratio (GOS-E £ 7)…”
supporting
confidence: 92%
“…24 The diagnostic performance of GFAP-BDP, as indicated in the current study by receiver operator curve analysis, is on a par with that of troponin in myocardial ischemia and brain natriuretic peptide in congestive heart failure. [25][26][27] Our findings are also consistent with previous reports in terms of predictive power and measured levels of serum GFAP in TBI. 4 We found that serum GFAP-BDP Odds ratio (GOS-E £ 7)…”
supporting
confidence: 92%
“…The largest analysis comes from the Acute Decompensated Heart Failure National Registry (ADHERE) (n ϭ 67924). Of these, 6% had increased cardiac troponin by the means of less conventional assays and by using rather high receiver operator characteristics curve-derived cutoffs (14 ). Increased cardiac troponin in this study was associated with more severe symptoms, a greater need for supportive measures including inotropic therapy and worse 30-day outcomes.…”
Section: Acute Cardiovascular Conditions Acute Decompensated Heart Famentioning
confidence: 63%
“…As shown in the present study, a structural myocardial protein, cardiac troponin, is released from damaged myocytes. On the other hand, the neurohormones BNP and NT-proBNP are released when hemodynamic stress increases, acting as a cardiac failure biomarker independent of hs-cTnI [31]. Furthermore, at times, their serum or plasma levels elevate concurrently, resulting in high mortality [30,32].…”
Section: Discussionmentioning
confidence: 99%